2018
DOI: 10.1016/j.microrel.2018.07.144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-circuit stress on the degradation of the SiO2 dielectric in SiC power MOSFETs

Abstract: This paper presents the impact of a short-circuit event on the gate reliability in planar SiC MOSFETs, which becomes more critical with increased junction temperature and higher bias voltages. The electrical waveforms indicate that a gate degradation mechanism takes place, showing a large gate leakage current that increases as the gate degrades more and more. A failure analysis has been performed on the degraded SiC MOSFET and then compared to the structure of a new device to identify possible defects/abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…For the third region (3), the device is placed under a small gate polarization (strong depolarization in Vgs), which generates an increase in Rds(on) and consequently losses in higher conduction. On the other hand, with a Vgs too close to Vgsth makes the device more sensitive to electron trapping effect at SiC/SiO2 interface and Vgsth drift [16][17]. Also, due to the variability of local Vgsth from one local MOSFET cell to another, a too low Vgs can lead to a high current density inhomogeneity of the chip surface in the channel regions.…”
Section: Failure Mode and Gate Voltage Depolarizationmentioning
confidence: 99%
“…For the third region (3), the device is placed under a small gate polarization (strong depolarization in Vgs), which generates an increase in Rds(on) and consequently losses in higher conduction. On the other hand, with a Vgs too close to Vgsth makes the device more sensitive to electron trapping effect at SiC/SiO2 interface and Vgsth drift [16][17]. Also, due to the variability of local Vgsth from one local MOSFET cell to another, a too low Vgs can lead to a high current density inhomogeneity of the chip surface in the channel regions.…”
Section: Failure Mode and Gate Voltage Depolarizationmentioning
confidence: 99%
“…These different post cracks were a clear marker of a permeant physical degradation of the device. Different studies show the presence of the gate damage failure mode [25,26], and the successive degradations [27]. However, some authors have shown that it is also possible to partially restore the gate-integrity by a dedicated original gate-bias procedure, in off-line operation, provided that the gate is not totally cracked [28].…”
Section: Sequencementioning
confidence: 99%
“…1D electro-thermal-metallurgical (Al) simulation highlighting different stress levels. [11,12,13] failures [11]. Afterwards the device enters an ageing region, where the gate starts to weaken until the devices reaches Al solidus to liquidus temperature range, 933K.…”
Section: The Benefits Of a Sub-microsecond Detectionmentioning
confidence: 99%